PENINGKATAN KUALITAS PROGRAM IKATAN PELAJAR MUHAMMADIYAH KIDS MELALUI IMPLEMENTASI SUPERVISI PENDIDIKAN DI MI MUHAMMADIYAH 1 JOMBANG - Mochammad Maulana Charis Chasbulloh; Muhammad Al-Fatih (STKIP Pesisir Selatan, 2026)
This study aims to examine and describe the improvement of the quality of the Ikatan Pelajar Muhammadiyah (IPM) Kids program through the implementation of educational supervision at MI Muhammadiyah 1 Jombang. IPM Kids is a cadre development and character-building program for elementary school students that focuses on developing leadership, discipline, responsibility, and the values of Al-Islam and Muhammadiyah (AIK). This study employed a qualitative approach with a case study design. The research participants consisted of the principal, IPM Kids advisors, teacher mentors, and students. Data were collected through participant observation, in-depth interviews, and documentation. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through source, technique, and time triangulation. The findings indicate that the quality of the IPM Kids program improved significantly, as reflected in more structured program implementation, increased student participation, enhanced leadership character, and stronger internalization of AIK values. These improvements were supported by the implementation of collaborative supervision involving planning, observation, constructive feedback, and continuous follow-up guidance.